Edith Jacobson papers - Jacobson, Edith
Correspondence, writings, artwork, and other papers chiefly relating to Jacobson's psychiatric practice, psychoanalysis, the study and treatment of depression, and object relations theory. Includes material on the psychological effects of imprisonment on female political prisoners based on Jacobson's experiences in Nazi Germany and her related and unpublished compilation of essays and short stories entitled, "An American Oak Tree."
German psychiatrist and psychoanalyst. Practiced in Berlin until imprisoned by the Nazis in 1935; escaped to the United States in 1938; continued to practice in New York, N.Y., from 1940 to 1977. Born 1897, died 1978.
Collection material in English and German.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Sigmund Freud collection.
Keywords: Depression, Mental; Imprisonment -- Psychological aspects; Object relations (Psychoanalysis); Political refugees -- Germany; Political refugees -- United States; Psychiatry -- Practice -- Germany -- Berlin; Psychiatry -- Practice -- New York (State) -- New York; Psychoanalysis; Women political prisoners -- Germany; Germany -- History -- 1933-1945.; Psychiatrists; Psychoanalysts